Multimodal Metaphors and Metonymies in Turkish Airlines’ Advertisements - Melike BAŞ (Dilbilim Araştırmaları Dergisi)
This study aims to investigate the verbal and pictorial metaphors as a kind of multimodal metaphors within the frame of cognitive linguistics (Forceville, 1996). For this purpose, a micro analysis of three advertisement posters of Turkish Airlines addressed to international passengers was carried out. The verbal and visual texts on the posters were examined within the multimodal metaphor analysis framework proposed by Forceville (1996, 2009) and developed by Pérez Sobrino (2017), and how the cognitive mechanisms in the posters reached the pragmatic effect was discussed. The findings of the study showed that the examined posters were designed in a way that emphasize the service quality of the company, highlight the concepts of modernization and globalization, and activate the senses of the passengers through several conceptual metaphors and metonymies.